Adult psychiatric inpatient admissions and length of stay before and during the COVID-19 pandemic in a large urban hospital setting in Vancouver, British Columbia - Russolillo, Angela; Carter, Michelle; Guan, Mejiao; Singh, Pulkit; Kealy, David; Raudzus, Julia (Frontiers in Health Services, 2024)
Introduction: During the COVID-19 pandemic individuals with mental illnesses faced challenges accessing psychiatric care. Our study aimed to describe patient characteristics and compare admissions and length of stay (LOS) for psychiatric-related hospitalizations before and during the COVID-19 pandemic. Methods: We conducted a retrospective analysis using health administrative data comparing individuals with an acute psychiatric admission between two time periods: March 1 st 2019 Dec. 31 st 2019 (pre-COVID) and March 1 st 2020 Dec. 31 st 2020 (during-COVID). Multivariable negative binomial regression was used to model the association between most responsible diagnosis type and the two-time periods to hospital LOS, reporting the Rate Ratio (RR) as measure of effect. Results: The cohort comprised 939 individuals who were predominately male (60.3%) with a severe mental illness (schizophrenia or mood-affective disorder) (72.7%) and a median age of 38 (IQR 28.0, 52.0) years. In the multivariable analysis, anxiety disorders (RR: 0.63, CI: 0.4, 0.99) and personality disorders (RR: 0.52, CI: 0.32, 0.85) were significantly associated with a shorter LOS when compared to individuals without those disorders. Additionally, when compared to non-substance-related disorders hospital admissions the LOS for patients with substance-related disorders were significantly shorter during the COVID period (RR: 0.45. CI: 0.30, 0.67) and pre-COVID period (RR: 0.31, CI: 0.21, 0.46). Conclusions: We observed a significant difference in the type and length of admissions for various psychiatric disorders during the COVID-19 period. These findings can support systems of care in adapting to utilization changes during pandemic or other global health events.